Effect of Time and Speed on the Performance of a Machine for Mixing Groundnuts Seeds with Additives - G., Olajide O.; Agbetoye, L. A. S (Local Engineering, 2026)
Studies that investigated the effectiveness of groundnut mixing as a function of mixing speed and time are scarcely reported. Therefore, the objective of the study is to investigate the main and interaction effects between additive and speed on the mixing evaluation parameters, with respect to different mixing proportions of ginger, wheat flour and pepper. The mixing parameters for evaluating the mixer are; degree of mixing, percentage loss and mixing efficiency. The components of the mixer consist of the frame, the U-shaped trough, a central shaft and a helical ribbon agitator. The coating unit consists of coating trough, drive shaft and electric motor. The highest values of the degree of mixing and mixing efficiency recorded were 92.23 and 99.75% respectively. The efficiency of mixing increases as mixing time increases. Similarly, increased performance in mixing was observed as the mixing speed increases. The main and interaction effects between the additive and speed were insignificant (P > 0.05). The highest speed of 60 rpm and mixing time of 15 mins produced the highest mixing efficiency.